Effect of Dietary Supplementation with Dried Olive Leaf Powder and L-Carnitine on Hematological and Biochemical Blood Parameters of Broiler Chickens (Ross 308) - Hayfaa Mohammed Salih, (American Journal of Botany and Bioengineering, 2026)
Natural feed additives have received increasing attention in poultry nutrition due to their potential role in improving physiological status and reducing metabolic disorders in broiler chickens. Olive leaves are rich in phenolic compounds and antioxidants, while L-carnitine plays an essential role in fatty acid metabolism and energy production. This study was conducted at the broiler chicken farm of the Animal Production Unit, College of Medicinal and Industrial Plants, University of Kirkuk, Iraq, from 9 September 2024 to 13 October 2023. A total of 180 broiler chicks (Ross 308) were used in the experiment. At 7 days of age, the birds were randomly allocated to six experimental treatments with three replicates each: T1 (control), T2 (1 g/kg dried olive leaf powder), T3 (2 g/kg dried olive leaf powder), T4 (500 mg/kg L-carnitine), T5 (1 g/kg dried olive leaf powder + 500 mg/kg L-carnitine), and T6 (2 g/kg dried olive leaf powder + 500 mg/kg L carnitine). Birds were fed a starter diet until 21 days of age followed by a grower diet until 35 days, with feed and water provided ad libitum. The results showed that dietary supplementation with dried olive leaf powder and L-carnitine, either individually or in combination, significantly improved several hematological and biochemical blood parameters compared with the control treatment. The supplemented treatments showed increased concentrations of total protein, albumin, and high-density lipoprotein (HDL), along with significant reductions in total cholesterol, triglycerides, low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL). In addition, the activities of liver enzymes aspartate aminotransferase (AST) and alanine aminotransferase (ALT) were reduced, indicating improved liver function and metabolic status. Moreover, lymphocyte percentage and the heterophil/lymphocyte (H/L) ratio were not negatively affected. Dietary supplementation with dried olive leaf powder and L-carnitine can improve biochemical blood parameters and metabolic health in broiler chickens (Ross 308), suggesting that these additives may serve as effective natural feed supplements in broiler production systems.